THE ENHANCEMENT OF MATHEMATICAL CRITICAL THINKING SKILLS AND SELF-EFFICACY AT SENIOR HIGH SCHOOL STUDENTS THROUGH LEARNING- BASED PROBLEMS CONTEXTUAL MODEL - Waode Listiani (USN Kolaka, 2016)
Critical thinking skills of mathematics (KBKM ) and self-efficacy (SE )of math students is still relatively low. This is due to the learning of mathematics in the classroom monotonous, so that students feel bored in learning mathematics, students' passive learning, and students are not self-sufficient in constructing knowledge and untrained students develop thinking ability. Learning model that predicted either to be applied to the study of mathematics and in order to encourage the emergence KBKM and SE math student is problem based learning model contextual (PBMK ). The purpose of this study is to improve KBKM and SE mathematics students through the application PBMK models. This research uses experimental design preetest-posttest control group design. The study population was all students in grade X SMAN 3 Kendari, samples were taken two classes by using purposive sampling and determination of the experimental class and control class chosen randomly. Students got a model experimental class and control class PBMK receive direct instructional model (PL ). The research instruments used were pretest and posttest for KBKM, SE scale and observation sheet. Data were analyzed by descriptive qualitative, ttest, analysis of randomized block design, and multivariate analysis. Based on the results of data analysis can be concluded that overall, KBKM and SE mathematics students who obtain PBMK models increase significantly higher than students who received the OT. Based on prior knowledge of mathematics students, the average increase KBKM and SE math students by category PAM (high, medium or low ), which received a model PBMK higher than the average increase in KBKM and SE math students by category PAM (high, medium or low ) who got the OT model. The results of the analysis of observational data indicate that the models PBMK can improve the students' learning activities.